Genetic diversity and phylogenetic relationships among western and Asian honey bees, and Eristalis tenax collected in Myanmar - Saw Bawm; Aye Pyae Pyae Khaing; Hlaing Min Oo; Myint Myint Mu; Ngwe Chi Hmuu; Aye Nyein Sandi Zaw; Nyunt Lwin; Hla Myet Chel; Yadanar Khaing; Shwe Yee Win; Lat Lat Htun; Shiro Murata; et al. (Journal of Asia-Pacific Entomology, 2025)

Confirmation of Skywalker Hoolock Gibbon (Hoolock tianxing) in Myanmar Extends Known Geographic Range of an Endangered Primate - Pyae Phyo Aung; Ngwe Lwin; Tin Htun Aung; Thura Soe Min Htike; Carolyn Thompson; Christian Roos; Sa Myo Zaw; L. Zawng Lum; Win Naing Oo; Zung Sau; Samuel T. Turvey; Wai Zinn Thein; et al. (International Journal of Primatology, 2024)
Characterizing genetically distinct populations of primates is important for protecting biodiversity and effectively allocating conservation resources. Skywalker gibbons ( Hoolock tianxing ) were first described in 2017, with the only confirmed population consisting of 150 individuals in Mt. Gaoligong, Yunnan Province, China. Based on river geography, the distribution of the skywalker gibbon has been hypothesized to extend into Myanmar between the N’Mai Kha and Ayeyarwaddy Rivers to the west, and the Salween River (named the Thanlwin River in Myanmar and Nujiang River in China) to the east. We conducted acoustic point-count sampling surveys, collected noninvasive samples for molecular mitochondrial cytochrome b gene identification, and took photographs for morphological identification at six sites in Kachin State and three sites in Shan State to determine the presence of skywalker gibbons in predicted suitable forest areas in Myanmar. We also conducted 50 semistructured interviews with members of communities surrounding gibbon range forests to understand potential threats. In Kachin State, we audio-recorded 23 gibbon groups with group densities ranging between 0.57 and 3.6 group/km 2 . In Shan State, we audio-recorded 21 gibbon groups with group densities ranging between 0.134 and 1.0 group/km 2 . Based on genetic data obtained from skin and saliva samples, the gibbons were identified as skywalker gibbons (99.54–100% identity). Although these findings increase the species’ known population size and confirmed distribution, skywalker gibbons in Myanmar are threatened by local habitat loss, degradation, and fragmentation. Most of the skywalker gibbon population in Myanmar exists outside protected areas. Therefore, the IUCN Red List status of the skywalker gibbon should remain as Endangered.

LP-08: Sodium Arsenite Attenuates the Cytoskeletal Gene Expression and Alters Morphology of Primarily Cultured Mouse Cortical Astrocytes - N.T.T. Htike; F. Maekawa; S. Kobayashi; S. Maejima; Z.H. Tun; T.T. Win-Shwe; S. Tsukahara (Toxicology Letters, 2023)

Online citizen science with the Zooniverse for analysis of biological volumetric data - Patricia Smith; Oliver N. F. King; Avery Pennington; Win Tun; Mark Basham; Martin L. Jones; Lucy M. Collinson; Michele C. Darrow; Helen Spiers (Histochemistry and Cell Biology, 2023)
Public participation in research, also known as citizen science, is being increasingly adopted for the analysis of biological volumetric data. Researchers working in this domain are applying online citizen science as a scalable distributed data analysis approach, with recent research demonstrating that non-experts can productively contribute to tasks such as the segmentation of organelles in volume electron microscopy data. This, alongside the growing challenge to rapidly process the large amounts of biological volumetric data now routinely produced, means there is increasing interest within the research community to apply online citizen science for the analysis of data in this context. Here, we synthesise core methodological principles and practices for applying citizen science for analysis of biological volumetric data. We collate and share the knowledge and experience of multiple research teams who have applied online citizen science for the analysis of volumetric biological data using the Zooniverse platform ( www.zooniverse.org ). We hope this provides inspiration and practical guidance regarding how contributor effort via online citizen science may be usefully applied in this domain.

How context affects transdisciplinary research: insights from Asia, Africa and Latin America - Flurina Schneider; Aymara Llanque-Zonta; Onintsoa Ravaka Andriamihaja; R. Ntsiva N. Andriatsitohaina; Aung Myin Tun; Kiteme Boniface; Johanna Jacobi; Enrico Celio; Clara Léonie Diebold; Laby Patrick; Phokham Latthachack; Jorge Claudio Llopis; et al. (Sustainability Science, 2022)
Transdisciplinary research (TDR) has been developed to generate knowledge that effectively fosters the capabilities of various societal actors to realize sustainability transformations. The development of TDR theories, principles, and methods has been largely governed by researchers from the global North and has reflected their contextual conditions. To enable more context-sensitive TDR framing, we sought to identify which contextual characteristics affect the design and implementation of TDR in six case studies in Asia, Latin America, and Africa, and what this means for TDR as a scientific approach. To this end, we distinguished four TDR process elements and identified several associated context dimensions that appeared to influence them. Our analysis showed that contextual characteristics prevalent in many Southern research sites—such as highly volatile socio-political situations and relatively weak support infrastructure—can make TDR a challenging endeavour. However, we also observed a high degree of variation in the contextual characteristics of our sites in the global South, including regarding group deliberation, research freedom, and dominant perceptions of the appropriate relationship between science, society, and policy. We argue that TDR in these contexts requires pragmatic adaptations as well as more fundamental reflection on underlying epistemological concepts around what it means to conduct “good science”, as certain contextual characteristics may influence core epistemological values of TDR.

Cryptic genetic divergence of the red dwarf rasbora, Microrasbora rubescens , in and around Inle Lake: implications for the origin of endemicity in the ancient lake in Myanmar - Yusuke Fuke; Yuichi Kano; Sein Tun; LKC Yun; Seint Seint Win; Katsutoshi Watanabe (Journal of Fish Biology, 2022)
Inle Lake, an ancient lake located in the Shan Plateau of Myanmar, is a biogeographically attractive region with high fish endemism. Some endemic species inhabit the lake as well as the surrounding areas. The genetic and ecological relationships between populations in the lake and surrounding areas provide important insights into the process underlying ichthyofaunal formation in Inle Lake. In this study, the authors focused on red dwarf rasbora Microrasbora rubescens , an endemic genus and species in this region, and estimated its population structure and evolutionary scenario based on genome‐wide polymorphism, mtDNA and geometric morphometric analyses using samples from Inle Lake and three areas surrounding the lake. The results showed that M. rubescens comprises at least three genetically divergent lineages (Inle, Heho and Hopong) with distinct geographic structures consistent with nuclear and mtDNA data. In contrast, there was no clear regional differentiation in morphology. The divergence time estimation based on mtDNA suggests that the Hopong lineage diverged at 2.7 Ma and the Inle and Heho lineages diverged at 1.9 Ma – consistent with the nuclear DNA results. The deep divergence observed in the endemic species supports the ancient history of ichthyofaunal development in this region. The distinct regional differentiation and morphological conservatism of this species might have been shaped by niche conservatism in stagnant water environments that limit dispersal and morphological diversification. Future comprehensive genetic and morphological analyses and comparisons for other native species should reveal the geographic and ecological processes that shaped the ichthyofauna in this region.

Influence of Climate Change on Flowering Time - Win Tun; Jinmi Yoon; Jong-Seong Jeon; Gynheung An (Journal of Plant Biology, 2021)

Indole and Derivatives Modulate Biofilm Formation and Antibiotic Tolerance of Klebsiella pneumoniae - Thanachaporn Yaikhan; Manatsanan Chuerboon; Natchapol Tippayatham; Nateekarn Atimuttikul; Taiyeebah Nuidate; Mingkwan Yingkajorn; Aung Win Tun; Hansuk Buncherd; Natta Tansila (Indian Journal of Microbiology, 2019)

Histone deacetylase inhibitors suppress transdifferentiation of gonadotrophs to prolactin cells and proliferation of prolactin cells induced by diethylstilbestrol in male mouse pituitary - Nandar Tun; Yasuaki Shibata; Myat Thu Soe; Myo Win Htun; Takehiko Koji (Histochemistry and Cell Biology, 2019)

Genome-wide linkage scan and association study of PARL to the expression of LHON families in Thailand - Nopasak Phasukkijwatana; Bussaraporn Kunhapan; Jim Stankovich; Wanicha L. Chuenkongkaew; Russell Thomson; Timothy Thornton; Melanie Bahlo; Taisei Mushiroda; Yusuke Nakamura; Surakameth Mahasirimongkol; Aung Win Tun; Chatchawan Srisawat; et al. (Human Genetics, 2010)